A inguinal hernia repair technique using stainless steel mesh grafting - Reynes L, Juan C; Zerboni, V; García Capurro, Rafael (Cirugía del Uruguay, 2020)
We indicate the cases of inguinal hernias, direct or oblique, recurrences, or any big herniason weak abdominal walls on which metalic implants should be used.